1997
DOI: 10.1016/s0022-5347(01)64931-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Technique of Percutaneous Tract Creation on Incidence of Renal Hemorrhage

Abstract: Improvements in the technique of percutaneous renal surgery have decreased the morbidity associated with these procedures. In our study use of balloon tract dilators led to less renal hemorrhage and lower transfusion rates compared to Amplatz dilation. Additionally, balloon dilation appears to be more rapid and avoids renal movement away from the surgeon, which occasionally occurs during Amplatz dilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(69 citation statements)
references
References 9 publications
1
66
0
2
Order By: Relevance
“…This would appear contrary to recent papers suggesting a lower transfusion rate with pneumatic dilation compared to multi-incremental techniques. 19,20 However, we have only reported a small number of cases and the dilation technique was on the whole poorly recorded.…”
Section: Complicationsmentioning
confidence: 99%
“…This would appear contrary to recent papers suggesting a lower transfusion rate with pneumatic dilation compared to multi-incremental techniques. 19,20 However, we have only reported a small number of cases and the dilation technique was on the whole poorly recorded.…”
Section: Complicationsmentioning
confidence: 99%
“…Michel et al [17] demonstrated that balloon dilatation method had decreased operative times, blood loss, and exposure to fluoroscopy. Davidoff et al [8] revealed that Amplatz dilatation had led to higher incidence of bleeding episodes relative to balloon dilatation. In a study by Kukreja et al [15] , Amplatz dilators, Alken telescopic metal dilators, and balloon dilators were compared, and lesser blood loss was reported with Amplatz dilators relative to other dilators without any statistically significant difference between dilators regarding blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…[7] With the development in balloon dilators, some studies also have demonstrated superiority of balloon dilators over Amplatz dilators. [8] In this article, we compared use of Amplatz, and balloon dilators in consideration of pre-, and postoperative values.…”
Section: Introductionmentioning
confidence: 99%
“…Hemoraji iğne girişinin yapıldığı andan operasyonun sonlandırıldı-ğı ana kadar herhangi bir süreçte olabilir. Dilatasyon tipi tercihiyle ilgili olarak balon dilatasyonun daha az kanamaya neden olduğu ancak sekonder vakalarda etkisinin zayıf olduğunu iddia eden ça-lışmalar olsa da bu konuda net bir fikir birliği mevcut değildir (20)(21)(22). Biz kliniğimizde amplatz dilatatör seti kullanmaktayız.…”
Section: Discussionunclassified